Study on tensile, bending, fatigue, and in vivo behavior of porous SHS–TiNi alloy used as a bone substitute. (12th February 2021) - Yasenchuk, Yuri; Marchenko, Ekaterina; Baigonakova, Gulsharat; Gunther, Sergey; Kokorev, Oleg; Gunter, Victor; Chekalkin, Timofey; Topolnitskiy, Evgeniy; Obrosov, Aleksei; Kang, Ji-hoon
Abstract: Intermetallic porous SHS–TiNi alloys exhibit tangled and specific stress–strain characteristics. This article aims to evaluate the findings emanating from experiments using standard and proprietary instruments. Fatigue testing under repeated complex loading was used to measure the total number of load cycles before failure of the SHS–TiNi samples occurred. Of the tested samples, seventy percent passed through 10 6 cycles without failure due to the reversible martensite transformation in the TiNi phase, one of the prevailing constituents of a multiphase matrix. The fractured surfaces were analyzed using scanning electron microscopy and confocal laser scanning instruments. Microscopy studies showed that the entire surface of the sample is concealed by miscellaneous strata that result from the SHS processand effectively protect the porous alloy in a corrosive environment. Numerous non-metallic inclusions, which are also attributed to the SHS reaction, do not have a significant impact on the deformation behavior and fatigue performance. In this context, the successful in vivo functioning of porous grafts assessed in a canine rib-plasty model allows the bone substitute to be congruentially deformed in the body without rejection or degradation; it thus has a long operational life, often greater than 17 ×10 6 (22 × 60 × 24 × 540) cycles. It acknowledges the potential benefits of SHS–TiNi as a superior osteoplastic material and its high resistance to corrosion fatigue.